Aplicación de la moneda funcional y su incidencia en los resultados expresados en moneda nacional en la empresa Metalbus S.A. - Aredo García, Erik Daniel (2020)
ABSTRACT This research is about “The application of the functional currency and its impact on the results expressed in national currency in the company Metalbus SA. in the period 2015 - 2016 - 2017 ”. Its purpose is to determine how the application of the functional currency affected the results expressed in national currency at empresa Metalbus SA. in the periods 2015 - 2016 - 2017. The study was carried out using reports from the Metalbus SA. company, whose main activity is the manufacture of bodies for transport units. Financial Statements reports were analyzed and financial ratios were applied. The functional currency for the subsidiary company Metalbus SA. They are the American dollars. Profit was analyzed after the income tax in functional currency “dollars”, 2017 profit is obtained, which amounts to $ 78,728 and a loss in 2016 and 2015 of $ 93,964 and $ 98,735. While in national currency (Sol) the following results S / 92,746, S / 146,015 and S / 679,886. The differences in the results between both currencies are due to the effect of the functional currency and the current tax regulations that require us to determine the results in soles. It was determined that the application of the functional currency has a significant financial impact on the results depending on the currency presented.